Family Economic Hardship and Adolescent Risk-Taking: The Mediating Role of Family Cohesion - Sari, Intan; Deshmukh, Arjun; Nishimura, Haruka (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the mediating role of family cohesion in the relationship between family economic hardship and adolescent risk-taking. Methods and Materials: A descriptive correlational research design was employed with a sample of 520 adolescents recruited from secondary schools in India, determined through Morgan and Krejcie’s sample size table. Data were collected using standardized self-report instruments: the Adolescent Risk-Taking Questionnaire (ARQ), the Economic Hardship Questionnaire (EHQ), and the Family Adaptability and Cohesion Evaluation Scales (FACES IV). Statistical analyses were conducted using SPSS-27 and AMOS-21. Pearson correlation coefficients were calculated to determine associations among variables, and Structural Equation Modeling (SEM) was performed to test the hypothesized mediation model. Model fit was evaluated using Chi-square, χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices. Findings: Results indicated that family economic hardship was positively correlated with adolescent risk-taking (r = .42, p = .001) and negatively correlated with family cohesion (r = −.40, p = .001). Family cohesion was inversely related to adolescent risk-taking (r = −.36, p = .002). The SEM analysis demonstrated adequate model fit (χ²/df = 2.17, GFI = .93, AGFI = .90, CFI = .95, TLI = .94, RMSEA = .048). Direct paths showed that family economic hardship significantly predicted adolescent risk-taking (β = .38, p = .001) and negatively predicted family cohesion (β = −.41, p = .001). Family cohesion negatively predicted adolescent risk-taking (β = −.29, p = .002). The indirect effect of economic hardship on risk-taking via cohesion was significant (β = .12, p = .006), supporting the mediation hypothesis. Conclusion: Findings highlight that family cohesion partially mediates the link between economic hardship and adolescent risk-taking. Strengthening family cohesion may buffer adolescents from the adverse effects of financial strain and serve as a practical target for interventions aimed at reducing risk behaviors.